Pengaruh Arus Kas Operasi dan Ukuran Perusahaan Terhadap Persistensi Laba - M.Riduan Abdillah; Astia Putriana; Riani Tami (At-Tadbir : jurnal ilmiah manajemen, 2021)
The purpose of this research is to empirically prove the effect of operating cash flow and firm size on earnings persistence. The method used in this research is a quantitative method. The population of this research is 108 food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange in 2016-2018. The sampling technique in this research used the purposive sampling method so that the number of sample data used in this research was 36 manufacturing companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange in 2016-2018. The variables in this research consisted of independent variables, namely operating cash flow and company size, while the dependent variable in this research was earnings persistence. The data analysis technique in this research used multiple linear regression analysis. The hypothesis testing of this research was conducted through the t-test with a significance level of 0.05, the F-test with a significance level of 0.05 and the coefficient of determination. The results of this research found empirical evidence that operating cash flow has a positive effect on earnings persistence while firm size has a negative effect on earnings persistence.Keywords: Operating Cash Flow, Firm Size, Earnings Persistence, Bursa Efek Indonesia